Bentuk Batang Dan Sifat Fisika Kayu Kelapasawit - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT Palm oil has emerged as an important product in both domestic and international trade, due to large palm plantation and high technology in palm oil processing. Problems encountered in maintaining the sustained palm oil production is the huge amount of waste obtained in field and palm oil mills. These by-products of palm oil industries are empty fruit bunches (EFB), pressed fruit fibers (PFF), shells, palm oil mill effluents (POME), trunks and fronds. Those waste are still under vigorous research for converting to the useful products. In terms of oil palm trunk which is left behind in the field after replanting, a study on stem form and important physical wood characterictics was organized. The research tried to supply data which related to economical aspects in utilizing the wood waste, namely fresh (initial) moisture content and wood specific gravity. Two palm oil trees were felled and cut in 1 m length according to ISO-3129-1975. Log diameter, bark free log diameter, bark thickness were measured. A British standard 373-1957 was employed for physical measurement. The results of the study show three variables of stem form, namely log diameter, bark free log diameter and bark thickness decrease from butt to the top. Their range are 41-71cm